2006
DOI: 10.1002/pmic.200600365
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G2/M targets for the MAP kinase pathway by functional proteomics

Abstract: Although the importance of the extracellular signal-regulated kinase (ERK) pathway in regulating the transition from G1 to S has been extensively studied, its role during the G2/M transition is less well understood. Previous reports have shown that inhibition of the ERK pathway in mammalian cells delays entry as well as progression through mitosis, suggesting the existence of molecular targets of this pathway in M phase. In this report we employed 2-DE and MS to survey proteins and PTMs in the presence versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The known substrate for MEK1/2 is ERK1/2 (7). The role of ERK activity during G 2 /M transition is not well understood, but ERK seems to function through a complex and indirect role on a small subset of G 2 /M phosphoproteins (55), and the downstream effectors of ERK, which are required for mitosis progression, remain to be determined (2). However, a specific inhibitor of ERK1/2 (FR180204) had no influence on the titers of either the passaged mutants or wild-type PrV.…”
Section: Discussionmentioning
confidence: 99%
“…The known substrate for MEK1/2 is ERK1/2 (7). The role of ERK activity during G 2 /M transition is not well understood, but ERK seems to function through a complex and indirect role on a small subset of G 2 /M phosphoproteins (55), and the downstream effectors of ERK, which are required for mitosis progression, remain to be determined (2). However, a specific inhibitor of ERK1/2 (FR180204) had no influence on the titers of either the passaged mutants or wild-type PrV.…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR pathway has been extensively studied by Proud and co‐workers with a recent review providing an excellent summary (Proud, 2007). The contribution of the MKK pathway to EF2 kinase phosphorylation and the explicit role this plays in cell cycle has recently been examined by Roberts and co‐workers who demonstrate that phosphorylation of Ser366 rises quickly upon G1 entry in a synchronized cell population in an MKK‐dependent manner (Roberts et al., 2006).…”
Section: Ef2 Ef2 Kinase and The Cell Cyclementioning
confidence: 99%
“…We employed two-dimensional electrophoresis to identify proteins exhibiting diminished phosphorylation in cells treated with CK2 inhibitors based on its capacity to fractionate thousands of individual protein variants, including separation of different phosphorylated forms of individual proteins, and its demonstrated ability to identify substrates for protein kinases such as MAP kinase. (50) To extend these studies, we generated inhibitor-resistant mutants of CK2(15) to evaluate whether the identified proteins are indeed direct substrates for CK2. Utilizing these strategies, we identified EEF1D, a translational elongation factor implicated as a potential prognostic indicator in cancer (including medulloblastoma(51) and esophageal carcinoma(52)) as a bona fide cellular target of CK2.…”
Section: Introductionmentioning
confidence: 99%